A Comparative Analysis of Consumption Theories by Harold Domar and Monzer Kahf and Their Impact on National Economic Policies - Nurjamil, Nurjamil; Athoillah, Anton (IAIN Syekh Nurjati Cirebon, 2024)
This study aims to compare the consumption theories of Harold Domar and Monzer Kahf, highlighting their differences and implications for national economic policies. The research uses a qualitative approach and a literature review method to analyse the theories through a descriptive-comparative framework. Harold Domar’s theory adopts a traditional economic perspective, emphasising the relationship between income, savings, and investment as drivers of consumption and economic growth. Domar’s model provides a solid foundation for fiscal and monetary policies that stimulate growth through investment and consumption. In contrast, Monzer Kahf’s theory presents a holistic approach rooted in Islamic principles, integrating psychological, social, and cultural factors into consumption behaviour. Kahf emphasises ethical consumption, moderation, and social justice, aligning economic activities with spiritual values and sustainability. His framework incorporates key Islamic concepts such as At-Tayyibat (all that is good) and Ar-Rizq (provisions from God), advocating for consumption that fulfils material and spiritual needs while avoiding extravagance (israf) and wastefulness (tabzir). The findings reveal that while Domar’s theory is highly relevant for data-driven economic analysis and traditional policy planning, Kahf’s approach offers an ethical and inclusive perspective that addresses contemporary challenges like environmental sustainability and social welfare. This study concludes that both theories when combined, provide a comprehensive basis for crafting sustainable and equitable national economic policies.Keywords: Harold Domar, Monzer Kahf, Consumption Theory, Economic Policy, Islamic Economics, Moderation, Sustainability